1995
DOI: 10.1148/radiology.194.2.7529936
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the prostate: race as a prognostic indicator in definitive radiation therapy.

Abstract: Black men have more aggressive prostatic tumors, a higher rate of metastasis, and a poorer survival rate than do white men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 0 publications
2
24
1
Order By: Relevance
“…3 The present analysis extends these observations in demonstrating that the association of black race with lower disease-speci®c survival is prognostically informative individually of other variables, for example, grade, stage, time period of diagnosis. Because within clinical stage categories blacks have higher tumor volume than whites, 16 it is possible that the clinical stage is too gross a measure of disease to adjust the risk across race.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…3 The present analysis extends these observations in demonstrating that the association of black race with lower disease-speci®c survival is prognostically informative individually of other variables, for example, grade, stage, time period of diagnosis. Because within clinical stage categories blacks have higher tumor volume than whites, 16 it is possible that the clinical stage is too gross a measure of disease to adjust the risk across race.…”
Section: Discussionsupporting
confidence: 71%
“…11 Potential partial explanations for varying outcomes by calendar time include variations in treated patient age, staging methods, and patterns of care, for example dissemination of external beam radiation in the early 1980s. 1,3,7,12 Regardless of whether or not calendar time effects are due to cohort effects, stages of diagnosis and treatment, patient selection, and/or technical modi®cations of treatments, they can signi®cantly confound efforts to estimate clinical outcomes and cannot be ignored. In generalizing the results of reports that group patients across many years, for example from 1956±1992, 1 one must be cautious.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Several reasons have been suggested, including socieoeconomic and cultural factors, cancer biology, differential treatment intensity, pharmacogenetics and comorbid conditions. [8][9][10][11][12] Data from hematologic malignancies such as AML also demonstrate poorer survival and worse CR rates in African Americans, specifically men, compared with African American women and whites.…”
Section: Introductionmentioning
confidence: 99%
“…Aziz et al, 59 found that black radiated patients were more likely to have Gleason sum of 7±10 which corresponded to higher stage and lower survival but multivariate analysis was not performed. Similarly, Kim et al, 60 studied 489 white and 157 black irradiation patients ®nding that 40% of blacks vs 26.% of whites (P`0.001) had poorly differentiated tumors. Blacks had signi®cantly worse overall survival and even with stage strati®cation, blacks with stage C disease had a worse cause-speci®c survival.…”
Section: Clinically Localized Prostate Cancer In African Americans Trmentioning
confidence: 97%